Case Report: Two Case Reports of Acute Myopericarditis After mRNA COVID-19 Vaccine - Sciaccaluga, Carlotta; D'Ascenzi, Flavio; Cameli, Matteo; Gallotta, Maddalena; Menci, Daniele; Antonelli, Giovanni; Banchi, Benedetta; Mochi, Veronica; Valente, Serafina; Focardi, Marta (Frontiers in Cardiovascular Medicine, 2022)
Background. Cases of myocarditis and myopericarditis after mRNA COVID-19 vaccines have been reported, especially after the second dose and in young males. Their course is generally benign, with symptoms onset after 24-72 hours from the dose. Case Summary. We report two cases of myopericarditis after the second dose of the mRNA-1273 COVID-19 vaccine in two young males. Both the patients were administered the mRNA-1273 COVID-19 vaccine from the same batch on the same day and experienced fever on the same day of the vaccine, and symptoms consisted of myopericarditis three days after the dose. Discussion. Myopericarditis is usually considered an uncommon adverse reaction after various vaccinations, reported also after the mRNA COVID-19 vaccine. Several explanations have been proposed, including an abnormal activation of the immune system leading to a pro-inflammatory cascade responsible for myocarditis development. The temporal aspect of these case reports is rather peculiar and it is useful to underscore that both vaccines belonged to the same batch of vaccines. However, despite these cases, vaccination against COVID-19 far outweighs the risk linked to COVID-19 infection and remains the best option to overcome this disease.